International Journal of Social Science and Business: Point Coffee’s Digital Communication Strategies Through Post Feeds Instagram @Pointcoffeeid - Mita Sari Kurniawan; Rewindinar Rewindinar (International Journal of Social Science and Business, 2021)
Many new brands are starting to enter the coffee business, one of which is Point Coffee. The emergence of a new coffee shop makes every business person compete to create an attractive brand image and unit to attract consumers' attention. Many coffee choices provide an alternative to buyers in determining purchasing decisions for the products to be used. Marketing is one way to increase product purchases, viz. In marketing, Point Coffee uses Instagram @pointcoffeeid. This article discusses how Point Coffee's digital communication strategy is implemented in @pointcoffeeid's Instagram post feed. This study analyses the Point Coffee digital communication strategy applied to the Instagram @pointcoffeeid Inpost Feed. The research method used is descriptive qualitative using netnographic methods. This analysis was carried out on Instagram content as a data source. The primary data in this study is the post feed content with 155 posts on the @pointcoffeeid Instagram feed. The data analysis technique used is descriptive qualitative and quantitative analysis. The results showed that Point Coffee carried out a digital communication strategy with awareness campaigns, promotions, collaborations, user-generated content campaigns, and product information. Point Coffee applies a photo posting strategy with a carousel. It is used to collaborate with existing strategies so that Point Coffee ensures product sales so that it can increase awareness and interaction between followers and the @pointcoffeid account.